Do components of adult height predict body composition and cardiometabolic risk in a young adult South Asian Indian population? Findings from a hospital-based cohort study in Pune, India: Pune Children's Study. Issue 10 (7th October 2020) - Kumaran, Kalyanaraman; Joshi, Suyog M; Di Gravio, Chiara; Lubree, Himangi; Joglekar, Charudatta; Bhat, Dattatray; Kinare, Arun; Bavdekar, Ashish; Bhave, Sheila; Pandit, Anand; Osmond, Clive; Yajnik, Chittaranjan; et al.
Abstract : Objectives: We investigated whether the relationship between components of height and cardiovascular disease (CVD) risk may be explained by body composition. We also examined relationships between parental heights and offspring CVD risk. Design: A cohort study using cross-sectional data. Setting: A secondary care hospital setting in Pune, India. Participants: We studied 357 young adults and their parents in the Pune Children's Study. Primary and secondary outcomes: we measured weight, total height, leg length, sitting height, plasma glucose, insulin and lipids, and blood pressure (BP). Total and regional lean and fat mass were measured by dual X-ray absorptiometry. Results: Leg length was inversely related, and sitting height was directly related to BMI. Total height and leg length were directly related to lean mass, while sitting height was directly related to both lean and fat mass. Leg length was inversely related to systolic BP and 120 min glucose, independent of lean and fat mass. Sitting height was directly related to systolic BP and triglycerides; these relationships were attenuated on adjustment for lean and fat mass. When examined simultaneously, greater leg length was protective and greater sitting height was associated with a more detrimental CVD risk profile. Conclusions: Shorter adult leg length and greater sitting height are associated with a more adverse CVD risk factor profile. The mechanisms need further study, but our findings suggest a role for lean and fat mass.